God. - Wood, W.Jay (Central problems of philosophy., 2014)
This book explores two foundational questions about God: are there adequate reasons to think that God exists and if God exists, what is God like. The first and main question of the book takes up epistemological concerns, focusing on arguments for and against the claim that theism is rationally justifiable. Metaphysical questions about God's nature, in particular God's knowledge and power, comprise the second part of the volume. These two questions are related since, if the concept of a God perfect in wisdom, power and goodness is incoherent, it cannot be reasonable to believe that God exists.